The Poetry of Janina Degutytė. A Dialogue with Tradition: The Aspect of Imagery - Tūtlytė, Rita (Literatūra, 2018)
[full article and abstract in Lithuanian; abstract in English] This article explores the artistic image of Janina Degutytė’s poetry through the aspect of the tradition of dialogue. The poet belongs to the generation of Soviet writers – these “nomads” who sought to find their “literary tribe” strived to fill the collective consciousness, depleted and hollowed out during the postwar period, with the memory of Lithuanian poetic culture and foreign literary sources. At the onset of her artistic eandevors, Degutytė was influenced by the poetics of Eduardas Mieželaitis: hyperbolized contrasts of the great and the little, a cosmic imagination, characteristic of the era of cosmic exploration, and a rhetoric bearing semblance to the style of a publicist or a columnist. A fundamental “discussion” with this particular tradition can be observed in works from the poet’s mature artistic period, wherein cosmic imagery originates from an inner, sensory perspective. Degutytė substantially takes over the poetic school of Salomėja Nėris: she brings back and continues the tradition of emotional lyricism and further develops the model of confessional poetry. These elements of the artistic image remain pivotal in all of the poet’s works. Neither are bypassed other influences along the road to recovering tradition: these are the meditational nocturnal poetry of Vincas Mykolaitis-Putinas and the symbolic motives, found in the art of Mikalojus Čiurlionis of the early 20th century, which substantiated the imagination capable of transforming the world. From the impression left by the verses of German poets Friedrich Hölderlin and Rainer Maria Rilke – the depiction of nature as an eternal homeland of man, the posing of ontological and existential questions, and the usage of the motives of perpetual sources, the all-holding hand, and ripening. It is implied that the dialogue that Degutytė’s artistic imagery holds with tradition can be associated with the movement of retrieving cultural memory, which is a feature of her generation. The individual artistic image of the poet, based on a Romantic and symbolic worldview, is startlingly multilayered and one that integrally fuses the abovementioned traditions.